LOX and Its Methylation Impact Prognosis of Diseases and Correlate with TAM Infiltration in ESCA. (31st August 2022) - Wu, Chuanqiang; Jiang, Bin; Wu, Zixiang; Dong, Lingjun; Sun, Keyi; Wu, Ming
Abstract : Background . ESCA is one of the digestive tract tumors with a high fatality. It is implicated in an intricate gene regulation process, but the pathogenesis remains ambiguous. Methods . The study used the packages of Limma from R software to analyze DEGs of ESCA in the GEO database and TCGA database. We employed the DAVID website for enrichment analysis, and the string database constructed the PPI network. Hub genes were identified from ESCA DEGs with Cytoscape MCODE. We evaluated the clinical relevance of LOX expression and its DNA methylation in the cBioPortal database and explored the roles of LOX in ESCA immunity, especially immune cell infiltration levels and immune checkpoint expression, by immunedeconv package of R software. Conclusions . The overexpression of LOX in ESCA is regulated by DNA hypomethylation; LOX overexpression or LOX hypomethylation can predict a worse prognosis in patients with ESCA. Besides, LOX may be involved in TIME regulation, promoting the infiltration levels and function of TAM. Hence, high LOX expression affected by DNA hypomethylation has an essential role in patients with ESCA, which may become an effective prognostic marker and therapeutic target.